2016
DOI: 10.1371/journal.pone.0156808
|View full text |Cite
|
Sign up to set email alerts
|

Population Estimation Using a 3D City Model: A Multi-Scale Country-Wide Study in the Netherlands

Abstract: The remote estimation of a region’s population has for decades been a key application of geographic information science in demography. Most studies have used 2D data (maps, satellite imagery) to estimate population avoiding field surveys and questionnaires. As the availability of semantic 3D city models is constantly increasing, we investigate to what extent they can be used for the same purpose. Based on the assumption that housing space is a proxy for the number of its residents, we use two methods to estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 119 publications
2
57
3
Order By: Relevance
“…Similar accuracy limitations have been reported in the production of the GHS-POP and the HRSL population datasets [10,17]. Even when several local studies have demonstrated that information on the building use has the potential to improve population distribution results [61,62], this remains a major source of limitation in the production of global population datasets, as it is not possible to derive detailed semantic information on the building use through remote sensing methodologies. Population datasets such as LandScan and WorldPop integrate land use and land cover covariates to improve their results; however, as mentioned above, this introduces global transferability limitations and applicability restrictions.…”
Section: Discussionmentioning
confidence: 54%
“…Similar accuracy limitations have been reported in the production of the GHS-POP and the HRSL population datasets [10,17]. Even when several local studies have demonstrated that information on the building use has the potential to improve population distribution results [61,62], this remains a major source of limitation in the production of global population datasets, as it is not possible to derive detailed semantic information on the building use through remote sensing methodologies. Population datasets such as LandScan and WorldPop integrate land use and land cover covariates to improve their results; however, as mentioned above, this introduces global transferability limitations and applicability restrictions.…”
Section: Discussionmentioning
confidence: 54%
“…Three-dimensional information from buildings (e.g., area and height of a building) is conducive to population estimation on a fine scale [43,44]. Building height could not objectively reflect the distribution of the population because of the influence of building types and building characteristics.…”
Section: Establishment Of Population Disaggregation Modelmentioning
confidence: 99%
“…The research results from the regression analysis of Lwin and Murayama [47] and Biljecki et al [48] suggested that building floor space has a strong, positive, and linear correlation with population. This study found that the total building floor space within a particular geographic area has a meaningful association with the number of the population in the area.…”
Section: Introductionmentioning
confidence: 99%